عملية اكتساب اللغة العربية لطلاب البرنامج المكثف لتعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج في ضوء فرضية كراشن - Saraswati, Ananda Nova (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
In the process of learning language there are two phenomena, namely language acquisition and language learning. As did the PKPBA UIN Malang institution in learning Arabic, there is acquisition and language learning. The process of formal language acquisition can be seen in the learning process in the classroom. As for the process of obtaining language naturally can be seen from the bi'ah lughawiyah held in each class. The purpose of this article is: (1) To describe the process of obtaining the language of PKPBA UIN Malang students according to krashen hypothesis theory. (2) Knowing the language acquisition activities of PKPBA UIN Malang students. The methods used in this article are interviews, questionnaires, observations, and documentation. The results in this article are: (1) The process of obtaining the language of STUDENTS of PKPBA UIN Malang in accordance with the five krashen hypotheses (the hypothesis of obtaining and learning the language, the natural sequence hypothesis, the monitoring hypothesis, the input hypothesis, and the affective filter hypothesis). (2) The language acquisition activities of PKPBA UIN Malang students are scientific debates, Arabic discussions, storytelling of daily activities, Arabic conversations, Arabic language competitions between classroom languages, and mukhayyam 'arabiy. كان مظاهران في تعليم اللغة العربية في البرنامج المكثف لتعيم اللغة العربية في الجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج، وهما اكتساب اللغة وتعلم اللغة. وكذلك في البرنامج المكثف لتعليم اللغة العربية، كان مظاهران في تعليم اللغة العربية أي اكتساب اللغة العربية وتعلمها. وظهرت عملية اكتساب اللغة العربية رسميا في عملية تعليم اللغة في الفصل. وقد ظهر أيضا اكتساب اللغة العربية طبيعيا بالبيئة اللغوية الموجودة في كل فصول الطلاب. أما أهداف هذا المقال أن تكون: (1) لوصف عملية اكتساب اللغة لطلاب البرنامج المكثف لتعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج بضوء فرضية كراشن. (2) لمعرفة أنشطة اكتساب اللغة العربية لطلاب البرنامج المكثف لتعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج. أما طريقة جمع البيانات المستخدمة في هذا المقال هي مقابلة، واستبانة، وملاحظة، وتوثيق. أما نتيجة المقال هي: (1) كانت عملية اكتساب اللغة العربية لطلاب البرنامج المكثف لتعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج مناسبة على فرضيات كراشن أي فرضية الكتساب اللغة وتعلمها، وفرضية الترتيب الطبيعي، وفرضية الرقابة، وفرضية المدخل، وفرضية المصفات الوجداني. (2) كانت أنشطة اكتساب اللغة العربية في البرنامج المكثف لتعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج هي: المناظرة العلمية، والمناقشة العربية، وتقديم القصة اليومية، والمحادثة بالعربية، والمسابقة العربية بين الفصول، والمخيم العربي.